Diagnostic challenges and prognostic implications of extranodal extension in head and neck cancer: a state of the art review and gap analysis - Henson, Christina E.; Abou-Foul, Ahmad K.; Morton, Daniel J.; McDowell, Lachlan; Baliga, Sujith; Bates, James; Lee, Anna; Bonomo, Pierluigi; Szturz, Petr; Nankivell, Paul; Huang, Shao Hui; Lydiatt, William M.; et al. (Frontiers in Oncology, 2023)
Extranodal extension (ENE) is a pattern of cancer growth from within the lymph node (LN) outward into perinodal tissues, critically defined by disruption and penetration of the tumor through the entire thickness of the LN capsule. The presence of ENE is often associated with an aggressive cancer phenotype in various malignancies including head and neck squamous cell carcinoma (HNSCC). In HNSCC, ENE is associated with increased risk of distant metastasis and lower rates of locoregional control. ENE detected on histopathology (pathologic ENE; pENE) is now incorporated as a risk-stratification factor in human papillomavirus (HPV)-negative HNSCC in the eighth edition of the American Joint Committee on Cancer (AJCC) and the Union for International Cancer Control (UICC) TNM classification. Although ENE was first described almost a century ago, several issues remain unresolved, including lack of consensus on definitions, terminology, and widely accepted assessment criteria and grading systems for both pENE and ENE detected on radiological imaging (imaging-detected ENE; iENE). Moreover, there is conflicting data on the prognostic significance of iENE and pENE, particularly in the context of HPVassociated HNSCC. Herein, we review the existing literature on ENE in HNSCC, highlighting areas of controversy and identifying critical gaps requiring concerted research efforts.